Theories for predicting simple solid solution high-entropy alloys: Classification, accuracy, and important factors impacting accuracy. (November 2020) - Li, Jian-Hong; Tsai, Ming-Hung
Abstract: This viewpoint paper reviews theories for predicting simple solid solution high-entropy alloys (HEAs). The models are first classified into two categories based on their core strategies, and representative models under each category are reviewed. One hundred HEAs are then selected from the literature and used to benchmark the accuracies of the models. The accuracies are compared, and factors that impact accuracy are pointed out and discussed. Some factors have global effects, while others affect specific groups of alloys. Important future directions to better assess these theories and to improve their accuracies are also proposed. Graphical abstract: Image, graphical abstract